Pumpkin in The Quran and Prophetic Ahadith , Its Antioxidant Benefits and Health Implications - Nurul Mukminah Zainan Nazri; Norhasnira Ibrahim; Wan Nasyrudin Wan Abdullah (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2025)
Non Index Publication (Tier 5)